Inovasi Media Digital Dalam Pembelajaran Pendidikan Agama Islam: Transformasi Pembelajaran Di Era Teknologi - Ebing Karmiza; Muhamad Faizul Amirudin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This research examines the innovation of digital media in Islamic Religious Education (IRE) learning, focusing on the transformation of educational practices in the digital era. The study aims to explore the role of digital media in enhancing the effectiveness and interactivity of IRE learning, as well as its impact on student engagement and understanding of Islamic teachings. The research employs a qualitative approach, utilizing case studies conducted in several high schools and universities that have integrated digital media into their IRE curriculum. Data were collected through interviews with teachers, students, and educational administrators, as well as direct observations of digital learning practices. The findings indicate that digital media, such as mobile apps, educational videos, and online platforms, significantly improve students' engagement and understanding of Islamic teachings. However, challenges such as limited digital literacy among educators and students, and insufficient infrastructure in some areas, were identified. This study highlights the potential of digital media to enhance IRE learning while emphasizing the need for further development of digital literacy skills and infrastructure to fully realize its benefits in education.